Continuous-flow hydrothermal and solvothermal synthesis of inorganic nanomaterials - Starkey, Christopher L. (2016)
Nanomaterials and nanotechnology are presently receiving high levels of interest which is aiding significant advancements to industrial and technological applications. New strategies towards nanoparticle synthesis are needed to produce high quality nanomaterials at industrially viable levels. This thesis presents the continuous flow hydrothermal and solvothermal synthesis (CFHSS) of a range of inorganic nanomaterials produced using a continuous-flow reactor designed at the University of Nottingham. The materials presented herein are currently industrially applicable or projected future trend materials. The aim is to widen the library of materials accessible via this relatively new synthetic strategy. It is mostly concerned with the development of the synthetic protocol towards specific materials and classes of materials, via both chemical and reactor configuration innovations, but additionally yields information about the chemical processes occurring within the reactor and how these can be controlled and exploited. This provides insight into not only the reactor but the field of CFHSS as a whole. Selected materials are subject to application based testing. With a fully industrial scale facility under construction, promising materials are trialled at pilot scale to assess the viability of the transfer of chemistry from laboratory to pilot scale with industrial scale production in mind. Chapter 1 provides an introduction to nanotechnology and nanomaterials in general, giving background to their unique properties and application. Traditional routes of synthesis are discussed, with particular focus then given to hydrothermal methods and continuous flow reactor design and nanoparticle production. Chapter 2 presents the characterisation techniques used in this thesis in terms of their theory and application. Application specific testing of the materials is explained in the relevant chapters. Chapter 3 reports the production of two different metal oxide materials, namely titania and doped titania photocatalyts, and barium strontium titanate nanopowders. Photocatalysis results are reported for the titania nanocrystals, and the barium strontium titanate nanopowders are produced in the first fully hydrothermal continuous flow synthesis at both laboratory and pilot scales to assess their viability for industrial scale production. Chapter 4 presents the development of the first continuous flow hydrothermal production of metal sulphide nanomaterials, via a general route using thiourea as the sulphur source. Full synthetic details and characterisation are discussed, together with information yielded about the materials and reactor and the implications this may have on future materials synthesis using CFHS and the Nottingham reactor. Chapter 5 details firstly batch hydrothermal and solvothermal synthesis of lithium iron phosphate materials to investigate the effect of a range of conditions on the reaction pathway and resulting products, followed by a translation of the knowledge learned into continuous flow hydrothermal and solvothermal reactions using the counter-current reactor. Scale up of the synthesis is achieved, together with electrochemical testing of selected products. Finally, chapter 6 provides general conclusions, summaries and outlooks for future work.